2010
DOI: 10.1016/j.meatsci.2009.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Tenderness – An enzymatic view

Abstract: One of the most common causes of unacceptability in meat quality is toughness. Toughness is attributed to a range of factors including the amount of intramuscular connective tissue, intramuscular fat, and the length of the sarcomere. However, it is apparent that the extent of proteolysis of key proteins within muscle fibres is significant determinant of ultimate tenderness. The objective of this manuscript is to describe the main endogenous proteolytic enzyme systems that have the potential to be involved in m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
232
0
17

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 349 publications
(258 citation statements)
references
References 83 publications
(124 reference statements)
9
232
0
17
Order By: Relevance
“…One of the most common causes of unacceptability in meat quality is toughness. It is attributed to various factors including the amount of intramuscular connective tissue, intramuscular fat, and the length of the sarcomere (Kemp et al 2010). Hou et al (2014) found that pelvic suspension increased sarcomere length.…”
Section: Warner-bratzler Shear Forcementioning
confidence: 99%
“…One of the most common causes of unacceptability in meat quality is toughness. It is attributed to various factors including the amount of intramuscular connective tissue, intramuscular fat, and the length of the sarcomere (Kemp et al 2010). Hou et al (2014) found that pelvic suspension increased sarcomere length.…”
Section: Warner-bratzler Shear Forcementioning
confidence: 99%
“…Despite the advantages in weight and carcass yield, the meat is considered extremely tough and somewhat bland due to low marbling (Goodson et al, 2001). Meat toughness can be attributed to high levels of calpastatin, which inhibit the calpain system -enzymes responsible for proteolysis of muscle post-mortem (Koohmaraie and Geesink, 2006;Kemp et al, 2010). "Callipyge" sheep meat presents significant decrease of myofibrillar fragmentation, indicative of a decrease in protein degradation (Hopkins et al, 2011).…”
Section: Genesmentioning
confidence: 99%
“…It was observed that in the ageing process one can distinguish changes in the micro and ultrastructure of muscle fi bers (weakening of myofi brils, fragmentation, changes in the area of the Z-line and the I-band) and degradation of myofi brillar and cytoskeletal proteins: T troponins, I troponins, titins, desmins, dystrophins, nebulins, vinculins, meta-vinkulins [Koohmaraie, 1992[Koohmaraie, , 1994Taylor et al, 1995a; tenderization if it meets certain basic criteria: proteases must be endogenous to skeletal muscle cells; they must be able to mimic postmortem changes in myofi brils in vitro and have access to myofi brils in a tissue. Investigations conducted by many researchers determined proteolytic systems present in a muscle which can participate in the postmortem proteolysis and tenderization: the system of calpains, cathepsins and proteasomes (mainly MPC -multicatalytic proteinase complex, called 20S proteasome) [Dransfi eld et al, 1992a,b;Koohmaraie, 1996;Korzeniowski et al, 1998;Kemp et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
“…Cathepsins are a group of enzymes comprising exo-and endo-peptidases and categorized into: cysteine (cathepsins B, H, L, X), serine (cathepsin G), and aspartic (cathepsins D, E) peptidase families [Sentandreu et al, 2002;Kemp et al, 2010].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation